Between Modernization and Marginalization: A Historical Analysis of Colonial Health Policies in Semarang and Their Postcolonial Legacy - Endah Sri Hartatik; Wasino; Vivek Neelakantan; Sukarni Suryaningsih; Ken Widyawati; Ilham Nur Utomo; Fortuna Devi Putri Sina (Paramita: Historical Studies Journal, 2025)
Abstract:  This article examines the population health policies implemented in Semarang City, Indonesia, in the aftermath of the Dutch colonial Ethical Policy (1901). Employing a social determinant of health framework grounded in a decolonial perspective, the study explores how colonial era policies continue to shape contemporary health practices and reinforce structural health inequalities. Drawing on historical methods and analysis of primary and secondary sources from national archives, libraries, and documentation centers, the research finds that the Ethical Policy—despite its humanitarian rhetoric of "repaying a debt of honor"—primarily served to sustain labor productivity for colonial economic interests. Health interventions such as the control of cholera outbreaks, the development of sanitation infrastructure, and hospital construction in Semarang were disproportionately directed toward protecting European residents and maintaining urban spatial segregation. These colonial legacies are still evident today in unequal access to healthcare, the geographic clustering of diseases, and the continued marginalization of local health knowledge systems. The article underscores the importance of applying approaches rooted in decolonization to the study of health systems in postcolonial contexts and calls for the development of more inclusive, historically grounded, and socially just health policies in Indonesia. Abstrak: Artikel ini mengkaji kebijakan kesehatan penduduk yang diterapkan di Kota Semarang, Indonesia, setelah diberlakukannya Politik Etis Belanda (1901). Dengan menggunakan kerangka social determinants of health dari perspektif dekolonial, penelitian ini menelusuri bagaimana kebijakan era kolonial terus membentuk praktik kesehatan kontemporer dan memperkuat ketidaksetaraan struktural di bidang kesehatan. Berdasarkan metode sejarah serta analisis sumber primer dan sekunder dari arsip nasional, perpustakaan, dan pusat dokumentasi, penelitian menemukan bahwa Politik Etis—meskipun mengusung retorika kemanusiaan “membayar hutang budi”—pada dasarnya ditujukan untuk mempertahankan produktivitas tenaga kerja demi kepentingan ekonomi kolonial. Intervensi kesehatan seperti pengendalian wabah kolera, pembangunan infrastruktur sanitasi, dan pendirian rumah sakit di Semarang lebih banyak diarahkan untuk melindungi penduduk Eropa dan menjaga segregasi spasial perkotaan. Warisan kolonial ini masih terlihat hingga kini dalam ketidakmerataan akses layanan kesehatan, pengelompokan geografis penyakit, serta marginalisasi sistem pengetahuan kesehatan lokal. Artikel ini menekankan pentingnya pendekatan dekolonisasi dalam kajian sistem kesehatan di konteks pascakolonial dan menyerukan pengembangan kebijakan kesehatan yang lebih inklusif, berlandaskan sejarah, dan berkeadilan sosial di Indonesia.